Review Essay: Coming to Grips with the Greenland Ice: Historical Flashbacks - Elzinga, Aant (Journal of Northern Studies, 2016)
Review of: Cornelia Lüdecke (hsg.), Verborgene Eiswelten. Erich von Drygalskis Bericht über seine Grönlandexpeditionen 1891, 1892–1893, München: August Dreesback Verlag 2015, ISBN 9783944334387, 476 pp.; Janet Martin-Nielsen, Eismitte in the Scientific Imagination. Knowledge and Politics at the Center of Greenland, New York: Palgrave Macmillan 2013, ISBN 9781137380791, 214 pp.